2016
DOI: 10.1093/geront/gnw125
|View full text |Cite
|
Sign up to set email alerts
|

A Social Model of Loneliness: The Roles of Disability, Social Resources, and Cognitive Impairment

Abstract: Purpose of the studyWe consider the points at which cognitive impairment may impact on the pathway to loneliness for older people, through impeding social interaction with family and friends, or by interfering with judgments concerning satisfaction with relationships.Design and methodsWe conceptualize a mediation model anticipating that social resources (LSNS-6) will mediate the pathway between disability (Townsend Disability Scale) and loneliness (De Jong Gierveld 6-item scale) and a moderated-mediation model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 50 publications
(57 reference statements)
1
65
0
1
Order By: Relevance
“…Therefore, it is essential to understand the circumstances under which older people are able to manage losses and experience good outcomes. Despite a corpus of research on cognitive processes including automatic comparison (Mussweiler et al 2004), unrealistic optimistic comparison (Bortolotti and Antrobus 2015) and resilience (Aburn et al 2016), theoretical and measurement models have not considered the moderating or mediating effect of psychological processes on the pathway between exclusion from social relations and outcomes for older people (for exceptions see, Burholt and Scharf 2014;Burholt et al 2016c), and further research is required in this area.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, it is essential to understand the circumstances under which older people are able to manage losses and experience good outcomes. Despite a corpus of research on cognitive processes including automatic comparison (Mussweiler et al 2004), unrealistic optimistic comparison (Bortolotti and Antrobus 2015) and resilience (Aburn et al 2016), theoretical and measurement models have not considered the moderating or mediating effect of psychological processes on the pathway between exclusion from social relations and outcomes for older people (for exceptions see, Burholt and Scharf 2014;Burholt et al 2016c), and further research is required in this area.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the evidence reviewed indicated that a clinical feature of dementia is a decline in social cognition including recognition of emotions (American Psychiatric Association 2013) and insight which in turn may contribute to a decline in social relations. However, the observed decline in social functioning is unlikely to be due to brain injury alone, but is also influenced by social dynamics such as cultural values, environmental accessibility and discrimination, psychological resources and socio-emotional processes such as sense of control or resilience (Burholt et al 2016c). Conversely, other reviews of research studies have demonstrated that loneliness (an outcome of exclusion from social relations) can lead to impaired cognitive function and decline over time (Cacioppo and Hawkley 2009;Hawkley and Cacioppo 2010).…”
Section: The Passage Of Time Interrelationships and Feedback Loopsmentioning
confidence: 98%
See 3 more Smart Citations